Rapid change in Yangtze fisheries and its implications for global freshwater ecosystem management. Issue 3 (28th February 2020) - Zhang, Hui; Kang, Myounghee; Shen, Li; Wu, Jinming; Li, Junyi; Du, Hao; Wang, Chengyou; Yang, Haile; Zhou, Qiong; Liu, Zhigang; Gorfine, Harry; Wei, Qiwei
Abstract: Freshwater capture fisheries are globally essential for food security and aquatic biodiversity conservation. The Yangtze River Basin is the third longest and one of the most human‐influenced drainage basins worldwide. Since the founding of P. R. China in 1949, this large river system has suffered increasing human perturbation and its sustainable development is now severely challenged. Meta‐analysis showed that Yangtze River fisheries have experienced an extraordinary process of utilization–over‐exploitation–protection during the past 70 years, to an extent that other globally important rivers may never have encountered. Its fisheries appear to have collapsed over the past four decades, with yield decreasing to only 25% of an historical peak of 400, 000 metric tonnes in the late 1950s. Endemic, migratory and rare fishes have been highly threatened with obvious changes in fish community structure and aquatic biodiversity. Anthropogenic activities, including impoundment of water in dams, discharge of pollutants and riverine modification for vessel navigation, have caused large decreases in fisheries yields. Projections from surplus production modelling showed potential for improvement under fishing ban scenarios, but without any prospect for full recovery to historical stock status. This study revealed that the change in fisheries resources was dominated by the social–ecological watershed system, and an integrated approach to river basin management is warranted. Better management of freshwater ecosystems to integrate food security with biodiversity conservation is urgently needed throughout the world, and the changes evident in the Yangtze River fish populations can serve as an informative global reference.